Why Do Prices in Sierra Leone Change So Often? : A Case Study Using Micro-level Price Data - Kovanen, Arto. (Washington, D.C. : International Monetary Fund, 2006)
We use cross-section and time-series techniques to analyze pricing behavior in Sierra Leone. In cross-sectional data, we find that inflation volatility and product diversification are the main factors explaining differences in the frequency of price adjustments. We show that variance in the fraction of prices subject to change is a key determinant of inflation volatility in Sierra Leone, indicating that retail prices are sensitive to economic events. We explain variations in this fraction over time with past inflation and monetary growth, which are important policy variables.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet